Effect of Different Infestation Levels of Chilo Infuscatellus (Snellen) on Quantity and Quality Parameters of Sugarcane - Raza Muhammad; Nazir Ahmad; Qadeer Ahmad; Maqsood Anwar Rustamani (Journal of Basic & Applied Sciences, 2012)
Population dynamics of sugarcane stem borer on commercial varieties of sugarcane were evaluated. The adults of Chilo infuscatellus (Snellen) emerged from over wintering larvae during fourth week of February. The population of adults of C. infuscatellus remained low in early vegetative growth stage of sugarcane crop. The number of moth/ trap increased gradually as the growth of the crop advanced and the maximum population of 37.4± 2.20 was recorded during August. When mean number of 18.98 moth/ trap were collected. The population of C. infuscatellus was declined after August and 28.6±2.42, 14.6 ± 1.74 moths were captured/ trap in month of September and October, respectively. The infestation of sugarcane stem borers was inversely proportional to the quantity and quality of sugarcane. Maximum cane weight of 13.5 ± 0.21 and 12.1± 0.05 kg were recorded in CPF-237 and Thatta-10 varieties at 0% infestation level, while minimum at 20% infestation (9.3±0.12 and 8.5 ±0.12 kg), respectively. Highest sugar recovery (11.0 ±0.08 and 10.2±0.11%) was observed at 0% infestation while lowest (9.3±0.12 and 8.5 ±0.12%) at 20% infestation in both the varieties.